2019
DOI: 10.1177/1066480719868705
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Family in Youth Opioid Misuse: A Literature Review

Abstract: Objective: With the opioid epidemic reaching declared a public health emergency in recent years, a synthesis of recent knowledge outlining the impact of opioid use disorders on youth and families is needed. To this aim, this exploratory literature review examined how the role of family is discussed in research on youth opioid misuse, with the goal of acting as a springboard for further research and treatment development that could mitigate the negative impacts opioids are having on families and youth. Method: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The interviews were intended to solicit participant experiences regarding OUD treatment, satisfaction with the medications used to treat OUD, counseling, current drug use, issues related to treatment retention (e.g. housing, legal problems, transportation, social support, family), goals and outlook [16,17]. The aim was to more clearly understand the factors, experiences and contexts that contributed to treatment retention, medication adherence, treatment re-entry, relapse and overdose.…”
Section: Methodsmentioning
confidence: 99%
“…The interviews were intended to solicit participant experiences regarding OUD treatment, satisfaction with the medications used to treat OUD, counseling, current drug use, issues related to treatment retention (e.g. housing, legal problems, transportation, social support, family), goals and outlook [16,17]. The aim was to more clearly understand the factors, experiences and contexts that contributed to treatment retention, medication adherence, treatment re-entry, relapse and overdose.…”
Section: Methodsmentioning
confidence: 99%
“…While more research is needed to better understand the relationship between SUD treatment and the utilization of FBT, it is possible that centers treating opioid use disorder (OUD) may also be the same sites that use the ASAM guidelines, which highlight the importance of family involvement in treatment for OUD (Kampman & Jarvis, 2015;Wong et al, 2020). Further, additional recent scholarship has highlighted the importance of the role of family in treatment for opioids (Kaur et al, 2019).…”
Section: Organizational Characteristicsmentioning
confidence: 99%
“…This recommendation is based on the protective effects that positive caregiver relationships have on young people’s substance use initiation and progression [ 21 ] and the effectiveness of family-based interventions (e.g., parent education, family counseling) in the prevention, early intervention, and treatment of young people’s substance use [ 21 , 22 ]. Nevertheless, few studies have investigated the role of caregivers in opioid use treatment and services for young people [ 23 ]. In a recent review, Kaur et al [ 23 ] identified two main foci in this scant literature, 1) ethical considerations and confidentiality when involving family members in young people’s opioid use treatment ( n = 3 studies), and 2) the benefits of family involvement ( n = 5 studies), including reduced rates of opioid use [ 24 ] and adherence to psychotherapeutic [ 25 ] and pharmacological treatments [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, few studies have investigated the role of caregivers in opioid use treatment and services for young people [ 23 ]. In a recent review, Kaur et al [ 23 ] identified two main foci in this scant literature, 1) ethical considerations and confidentiality when involving family members in young people’s opioid use treatment ( n = 3 studies), and 2) the benefits of family involvement ( n = 5 studies), including reduced rates of opioid use [ 24 ] and adherence to psychotherapeutic [ 25 ] and pharmacological treatments [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%